Spring flood induced shifts in Fe speciation and fate at increased salinity. (October 2019) - Herzog, S.D.; Conrad, S.; Ingri, J.; Persson, P.; Kritzberg, E.S.
Abstract: Rivers have traditionally been viewed as negligible sources of iron (Fe) to marine waters, as most Fe gets lost during estuarine mixing. However, recent findings demonstrate that Fe from boreal rivers display a higher resistance towards salinity-induced aggregation, presumably due to stabilizing interactions with organic matter. Previous studies have shown that Fe (oxy)hydroxides are selectively removed by aggregation processes, and that organic Fe complexes are less affected by increasing salinity. It has been further proposed that Fe speciation varies in response to seasonal differences in hydrology. In this study X-ray absorption spectroscopy (XAS) was used to determine the temporal variation in Fe speciation and the connection to Fe stability in response to increasing salinity in two boreal rivers (Kalix and Råne River), with the purpose to better understand the fate of riverine Fe export. Sampling was done from winter pre-flood, over the spring flood, to post-flood conditions (early April until mid June). In addition, parallel analyses for Fe speciation and isotope composition (δ 56 Fe relative to IRMM-14) were made on river samples, as well as salinity-induced aggregates and the fraction remaining in suspension, with the main objective to test if δ 56 Fe reflect the speciation of Fe. The contribution of organically complexed Fe increased during spring flood compared to the pre- and post-flood, as did Fe transport capacity. However, since Fe (oxy)hydroxides were dominating throughout the sampling period, the seasonal variability was small. Interestingly, salinity-induced aggregation experiments revealed that Fe (oxy)hydroxides, which dominated aggregates, displayed lower δ 56 Fe than in the river samples Fe, while organic Fe complexes in suspension had higher δ 56 Fe values. The seasonal variability in Fe isotope signature could not be simply linked to Fe speciation, but was probably also influenced by variation in source areas of Fe and processes along the flow-path that alter both Fe speciation and isotopic composition. Graphical abstract: Image 1 Highlights: Flow regime induces shift in riverine Fe speciation. Fe transport capacity at increased salinity is dependent on Fe speciation. Salinity induced removal of isotopically lighter Fe oxyhydroxides.